The life experiences of Turkish mothers who have children with an autism spectrum disorder - GÜLEÇ ASLAN, Yeşim (Advances in Social Sciences Research Journal, 2017)
This phenomenological study explored the experiences of 11 mothers who have children with an autism spectrum disorder (ASD) in Turkey. Content analysis of data from interviews emerged three themes. They include response to ASD diagnosis, living with ASD, and future perceptions. The findings indicated that the participating Turkish mothers showed negative responses after the diagnosis; potential factors could be influential on these responses; the mothers use coping strategies. Also, mothers shared their future needs These findings, which are hoped to contribute to the limited research literature on the life experiences of mothers, are discussed within the context of cultural elements in this study. The results discussed in terms of implications for future research and practices Keywords: Autism spectrum disorders, mothers, phenomenology, qualitative research